Penerapan Strategic Approach Pada Kegiatan Company Visit PT. Garuda Maintenance Facility Aero Asia Tbk - Adissa Irawaty; Aat Ruchiat Nugraha (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
PT Garuda Maintenance Facility Aero Asia Tbk (GMF) is a company engaged in aircraft maintenance, repair and overhaul (MRO). GMF has a business unit consisting of comprehensive aircraft maintenance, such as commercial aircraft maintenance, military aircraft maintenance and industrial services. At this company, the author took part in practical work activities in the Corporate Communications & CSR unit which is under the auspices of the Corporate Secretary & Legal service which carries out the public relations function at GMF. In this report, the author will explain the application of 4 strategic approaches to company visits held for GMF stakeholders using interview, observation and literature study methods. The stakeholder aspects that will be explained from the perspective of Grunig's 4 Linkage Model are functional linkage, enabling linkage, normative linkage, and diffused linkage. PT GMF approaches stakeholders using 4 strategic approaches, namely assertive, defensive, collaborative and responsive.